Cambridge IGCSE Mathemaics - Paul Metcalf (Collins IGCSE series., 2006)
Innovative, Interactive, International. Collins IGCSE Mathematics has been developed to give maximum support for students studying for the Cambridge International Examinations GCSE. International examples are used throughout, 'localising' learning. An interactive CD ROM, supporting study and revision, is included.